The Role of CREB in Depression and Antidepressant Treatment - Blendy, Julie A. (Biological psychiatry (1969), 2006)
Major depressive disorder is a severe clinical problem across the globe, with a lifetime risk of 10%–30% for women and 7%–15% for men. The World Health Organization ranks major depression at the top of the list in terms of disease burden, and this burden is expected to rise in the next decade as the prevalence of the disorder grows. Since the late 1950s, a wide range of antidepressant medications targeting the monoamine systems has been available to alleviate the symptoms of major depressive disorder. Although widely prescribed, such antidepressant medications are accompanied by a delay in effectiveness, as well as varied side effects. Therefore, further characterization of the biological mechanisms behind their function is crucial for the development of new and more effective treatments. One protein that could serve as a convergence point for multiple classes of antidepressant drugs is the transcription factor CREB (cyclic adenosine monophosphate response element binding protein). CREB is upregulated by chronic antidepressant treatment, and increasing CREB levels in rodent models results in antidepressant-like behaviors. Furthermore, postmortem studies indicate that CREB levels are increased in subjects taking antidepressants at the time of death. However, not all antidepressants increase CREB levels and/or activity, and reducing CREB levels in some brain regions also results in antidepressant-like behaviors. This review attempts to consolidate the information relevant to the structure and function of the CREB protein and describe how this relates to the mechanism of antidepressant drugs. Animal models in which CREB function is enhanced, by overexpression of the protein, or reduced, by expression of mutant forms of the protein or through gene deletion experiments, are summarized in terms of identifying a role for CREB in behavioral responses in depression tests that were originally designed to evaluate antidepressant efficacy. Human postmortem and genetic studies that implicate CREB in depression and antidepressant efficacy are also discussed.